2021
DOI: 10.1136/bmjophth-2021-000760
|View full text |Cite
|
Sign up to set email alerts
|

Living with heritable retinoblastoma and the perceived role of regular follow-up at a retinoblastoma survivorship clinic: ‘That is exactly what I have been missing’

Abstract: ObjectiveTo explore living with heritable retinoblastoma, specifically survivors’ perceived role of regular follow-up at a retinoblastoma survivorship clinic.Methods and analysisAdult survivors of heritable retinoblastoma were recruited from the Retinoblastoma Survivorship Clinic, Aarhus University Hospital. Ten survivors participated in individual explorative, semistructured interviews. Thematic data analysis was conducted.ResultsFive key themes relating to vision, social life, family, second cancer risk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…As reported previously, all participants consistently expressed a desire to avoid passing on the condition to their children (Gregersen et al, 2021). The present analysis shows how, for several participants, this concern was extremely strong.…”
Section: A Desire To Prevent Rb: "I Don't Wish the Same For My Child"supporting
confidence: 85%
See 2 more Smart Citations
“…As reported previously, all participants consistently expressed a desire to avoid passing on the condition to their children (Gregersen et al, 2021). The present analysis shows how, for several participants, this concern was extremely strong.…”
Section: A Desire To Prevent Rb: "I Don't Wish the Same For My Child"supporting
confidence: 85%
“…An explorative, qualitative study design (Kvale & Brinkmann, 2009; O'Reilly, 2012) was undertaken to obtain in‐depth insights into the lived experience of RB survivors (Gregersen et al, 2021). For the present analysis, a subset of data specifically regarding the reproductive choices in heritable RB was further analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of survivors of heritable pediatric retinoblastoma identified exacerbated fear of subsequent malignancies even though most participants did not remember their initial diagnosis. 20 These two syndromes feature a narrow set of affected organs and distinct patterns of cancer onset. Little is known about how AYAs with more variable cancer risk understand and experience survivorship.…”
Section: Survivorship For Ayas With Genetic Cancer Risk Syndromesmentioning
confidence: 99%
“…Other communities have not adopted similar language. A study of survivors of heritable pediatric retinoblastoma identified exacerbated fear of subsequent malignancies even though most participants did not remember their initial diagnosis 20 . These two syndromes feature a narrow set of affected organs and distinct patterns of cancer onset.…”
Section: Introductionmentioning
confidence: 99%